PENINGKATAN PENGETAHUAN TENTANG NUTRISI IBU NIFAS MENGGUNAKAN MEDIA APLIKASI â€œSINNIAâ€ DI RUMAH SAKITAURA SYIFA KEDIRI - Rahajeng Siti Nur Rahmawati; Suwoyo Suwoyo; Sinnia Fauziah Putri (JURNAL KEBIDANAN KESTRA (JKK), 2019)
The Lack of knowledge of mothers about the nutrition of childbirth mothers, causing the existence of understanding tarak. Smartphones equipped with the application "SINNIA" as a media for health promotion are expected to be able to facilitate postpartum mothers to more easily receive and understand information about the nutrition of postpartum mothers. The purpose of this study was to determine the effect of health education using the application media "SINNIA" on the knowledge of postpartum mothers at Aura Syifa Hospital 'Kediri. This research is a experimental study with the Pretest-Postest One Group type. The sampling technique used is non probability random sampling. The sample in this study was 20 mothers who matched the inclusion and exclusion criteria carried out in April 2019. Thus it can be concluded that there was the effect of health education using the application media "SINNIA" on nutrition knowledge for postpartum mothers at Aura Syifa Hospital 'Kediri. To further researchers who are interested in replicating this study, it is recommended that the experimental design be improved by adding control groups, improving the implementation of the intervention procedure, and improving the research instrument by adding items and adding alternative answers to 5. Health workers are advised to use the application "SINNIA" as an alternative way to facilitate the delivery of health information.